Hybridization of Triphenylamine and Salicylaldehyde: A Facile Strategy to Construct Aggregation‐Induced Emission Luminogens with Excited‐State Intramolecular Proton Transfer for Specific Lipid Droplets and Gram‐Positive Bacteria Imaging. Issue 14 (7th February 2020) - Yin, Wei; Li, Yue; Li, Nan; Yang, Weiyao; An, Hao; Gao, Jinrui; Bi, Yu; Zhao, Na
Abstract: Aggregation‐induced emission luminogens (AIEgens) with excited‐state intramolecular proton transfer (ESIPT) process have attracted significant attention in bioimaging applications owing to their high solid‐state emission efficiencies and large Stokes shifts. Herein, a series of simple AIEgens with ESIPT process, referred to as triphenylamine salicylaldehyde (TS) derivatives, are designed and synthesized by a rational hybridization of triphenylamine and salicylaldehyde units as the intramolecular rotor and ESIPT generator, respectively. Owing to the AIE and ESIPT effects, TS derivatives exhibit intense emission and large Stokes shifts (>140 nm) in the aggregated state. By altering the substituents in the triphenylamine units, their solid‐state emission varies from 490 to 590 nm. Owing to their excellent biocompatibilities and suitable lipophilicities, the TS derivatives are able to specifically and rapidly (<5 min) stain the lipid droplets in the cells in a wash‐free manner and successfully image the lipid‐rich tissue in vivo. Moreover, owing to their suitable hydrophilicity, TS and methoxyl substituted TS (TS‐OMe) are shown to stain gram‐positive bacteria with high selectivity. Abstract : A series of simple aggregation‐induced emission luminogens with excited‐state intramolecular proton transfer process (TS derivatives) are constructed by hybridizing triphenylamine and salicylaldehyde units, which can specifically stain the lipid droplets in living cells and lipid‐rich tissue in vivo. Both TS and TS‐OMe were also able to image gram‐positive bacteria with high selectivity.